The Effect of Using English Crossword Puzzle Application on Students’ Vocabulary Mastery in SMAS Adabiah Padang - Zultin, Salsa Fadila; Hanifa, Rizaldy (Journal of English Language Teaching, 2024)
This study aimed to figure out if there is a significant improvement of using English crossword puzzle application on students’ vocabulary mastery in SMAS Adabiah Padang. This study used pre- experimental with one- group Pretest- Posttest design. The researcher chose 34 students from XI MIPA 3. To compile the data, researchers used test (pretest and posttest) as instrument. The results of the study indicated that the utilized of English crossword puzzle application improved students’ vocabulary mastery. The students’ score before getting treatment was 48.94 then, after getting treatment students’ score increased to 69.62. They also enjoyed the learning atmosphere while English Crossword Puzzle Application was being implemented. Therefore, English Crossword Puzzle is good learning media to help English students enhance their vocabulary development.